Landscape of Individual Muslim Giving in Malaysia: an Analysis - Arifin Md. Salleh; Abdul Halim Mohd Noor; Hassan Bahrom; Abdul Rahim Ridzuan; Hamidah Irfan (Media Syari'ah, 2020)
The landscape of donor funding for international development appears to be changing significantly. Private philanthropic donors are playing an increasingly important role. The list in World Giving Index was shown that Malaysia has been in 71 ranking on world giving index in 2013. This paper provides insight into the characteristics of individual Muslim in Malaysia towards giving. Data were collected via online approach, 556 questionnaires were received. The result shows donors’ satisfaction and level of well being do influence tendency to donate. While the transparency issue, and attitude do not influence the decision to donate. This is due to high donor trust and consequently less demand on transparency. For demographic factors four variables significant to determine behavior of giving: gender; age; level of income and education background of the respondent. Further research in this area should attempt to make cross-cultural comparisons of donor characteristics. This would provide a more holistic perspective on donor behavior.